More Feedback Is Better than Less: Learning a Novel Upper Limb Joint Coordination Pattern with Augmented Auditory Feedback - Fujii, Shinya; Lulic, Tea; Chen, Joyce L. (Frontiers in Neuroscience, 2016)
Motor learning is a process whereby the acquisition of new skills occurs with practice, and can be influenced by the provision of feedback. An important question is what frequency of feedback facilitates motor learning. The guidance hypothesis assumes that the provision of less augmented feedback is better than more because a learner can use his/her own inherent feedback. However, it is unclear whether this hypothesis holds true for all types of augmented feedback, including for example sonified information about performance. Thus, we aimed to test what frequency of augmented sonified feedback facilitates the motor learning of a novel joint coordination pattern. Twenty healthy volunteers first reached to a target with their arm (baseline phase). We manipulated this baseline kinematic data for each individual to create a novel target joint coordination pattern. Participants then practiced to learn the novel target joint coordination pattern, receiving either feedback on every trial i.e. 100% feedback (n = 10), or every other trial, i.e. 50% feedback (n = 10) (acquisition phase). We created a sonification system to provide the feedback. This feedback was a pure tone that varied in intensity in proportion to the error of the performed joint coordination relative to the target pattern. Thus, the auditory feedback contained information about performance in real-time (i.e. “concurrent, knowledge of performance feedback”). Participants performed the novel joint coordination pattern with no-feedback immediately after the acquisition phase (immediate retention phase), and on the next day (delayed retention phase). The root-mean squared error (RMSE) and variable error (VE) of joint coordination were significantly reduced during the acquisition phase in both 100% and 50% feedback groups. There was no significant difference in VE between the groups at immediate and delayed retention phases. However, at both these retention phases, the 100% feedback group showed significantly smaller RMSE than the 50% group. Thus, contrary to the guidance hypothesis, our findings suggest that the provision of more, concurrent knowledge of performance auditory feedback during the acquisition of a novel joint coordination pattern, may result in better skill retention.